(untitled) - Prentis, Steve (London, 1984)
The chemistry of life and the key to biotechnology; Genetic engineering - reweaving the threads of life; Fermentation and selection - putting microbes to work; Biotechnology and disease - prevention, diagnosis and cure; The new green revolution; Biotechnology from farm to supermerket...
Keywords: Công nghệ sinh học,Biotechnology